Temporal profile of inflammatory response to fracture and hemorrhagic shock: Proposal of a novel long‐term survival murine multiple trauma model. Issue 7 (31st March 2015) - Kleber, Christian; Becker, Christopher A.; Malysch, Tom; Reinhold, Jens M.; Tsitsilonis, Serafeim; Duda, Georg N.; Schmidt‐Bleek, Katharina; Schaser, Klaus D.
ABSTRACT Hemorrhagic shock (hS) interacts with the posttraumatic immune response and fracture healing in multiple trauma. Due to the lack of a long‐term survival multiple trauma animal models, no standardized analysis of fracture healing referring the impact of multiple trauma on fracture healing was performed. We propose a new long‐term survival (21 days) murine multiple trauma model combining hS (microsurgical cannulation of carotid artery, withdrawl of blood and continuously blood pressure measurement), femoral (osteotomy/external fixation) and tibial fracture (3‐point bending technique/antegrade nail). The posttraumatic immune response was measured via IL‐6, sIL‐6R ELISA. The hS was investigated via macrohemodynamics, blood gas analysis, wet‐dry lung ration and histologic analysis of the shock organs. We proposed a new murine long‐term survival (21 days) multiple trauma model mimicking clinical relevant injury patterns and previously published human posttraumatic immune response. Based on blood gas analysis and histologic analysis of shock organs we characterized and standardized our murine multiple trauma model. Furthermore, we revealed hemorrhagic shock as a causative factor that triggers sIL‐6R formation underscoring the fundamental pathophysiologic role of the transsignaling mechanism in multiple trauma. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:965–970, 2015.